The Implementation of the Ottoman Method in Adult Quran Learning at the Talaqi Madani Quran Memorization House - Maisaro, Siti; Rena, Syahidah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
This study examines the implementation of the Ottoman Method in adult Quran learning at the Talaqi Madani Quran Memorization House, South Jakarta. Employing a qualitative research design with a phenomenological orientation, the study explores instructional practices, learner experiences, and institutional evaluation procedures associated with the method. Data were collected through in-depth interviews, classroom observations, document analysis, and a descriptive review of institutional evaluation records. The findings indicate that the Ottoman Method is implemented through a structured, level-based instructional system supported by placement testing, standardized learning materials, guided recitation (talaqqi), immediate corrective feedback, and periodic level-promotion evaluation. Adult learners demonstrated attainment of institutionally defined competency standards, while minor recitation errors—particularly in waqf and ibtida’ at intermediate levels—remained evident. Rather than making causal claims about instructional effectiveness, this study provides a contextualized account of how recitation development is supported and documented within a non-formal Quran education setting. The findings highlight the continued relevance of structured, teacher-guided instruction for adult Quran learning and contribute empirical insight into the implementation of the Ottoman Method in practice. Abstrak Penelitian ini mengkaji implementasi Metode Utsmani dalam pembelajaran Al-Qur’an bagi pembelajar dewasa di Rumah Tahfidz Al-Qur’an Talaqi Madani, Jakarta Selatan. Penelitian ini menggunakan pendekatan kualitatif dengan orientasi fenomenologis untuk mengeksplorasi praktik pembelajaran, pengalaman pembelajar, serta prosedur evaluasi institusional yang terkait dengan penerapan metode tersebut. Data dikumpulkan melalui wawancara mendalam, observasi kelas, analisis dokumen, dan telaah deskriptif terhadap catatan evaluasi lembaga. Hasil penelitian menunjukkan bahwa Metode Utsmani diterapkan melalui sistem pembelajaran terstruktur berbasis level yang didukung oleh tes penempatan, bahan ajar standar, pembacaan terbimbing (talaqqi), umpan balik korektif secara langsung, serta evaluasi kenaikan level secara berkala. Pembelajar dewasa menunjukkan pencapaian standar kompetensi yang ditetapkan oleh lembaga, meskipun masih ditemukan kesalahan minor dalam aspek tertentu, khususnya waqaf dan ibtida’ pada level menengah. Tanpa mengajukan klaim kausal mengenai efektivitas, penelitian ini menyajikan gambaran kontekstual tentang bagaimana perkembangan kemampuan membaca Al-Qur’an didukung dan didokumentasikan dalam lingkungan pendidikan Al-Qur’an nonformal. Temuan ini menegaskan relevansi pembelajaran terstruktur berbasis bimbingan guru bagi pembelajar dewasa serta memperkaya kajian empiris mengenai penerapan Metode Utsmani dalam praktik.